The effect of routine lymphadenectomy of the hepatic basin on the duration of the liver resection due to colorectal carcinoma metastases - Basarić, Dragan D; Soldatović, Ivan; Lekić, Nebojša S; Djordjević, Vladimir; Djurašić, Ljubomir; Micev, Marjan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Today, lymphatic metastases are only a relative contraindication for the surgical treatment of colorectal carcinoma (CRC). The aim of this study was to evaluate the effect of routine lymphadenectomy of the hepatic basin on the duration of the liver resection for CRC metachronous liver metastases. Methods. A total of 50 patients with CRC metachronous liver metastases underwent the liver resection with routine hepatic basin lymphadenectomy. Results. Larger volume of metastases (in mL), the number of affected segments, and the number of metastases as well the diameter of the largest lesion (in mm), determine the duration of the liver resection itself and the surgical procedure overall. The duration of lymphadenectomy was 25–55 min (32.2 min on average). Conclusion. Routine lymphadenectomy of the hepatic basin following the liver resection for CRC metachronous liver metastases, minimally prolongs the duration of the operation.